2016
DOI: 10.1111/lasr.12202
|View full text |Cite
|
Sign up to set email alerts
|

Privacy, CCTV, and School Surveillance in the Shadow of Imagined Law

Abstract: How do managers make decisions that affect human rights of other people? The article examines one such case: the decision‐making process of Israeli school principals in installing Closed Circuit TV (CCTV) systems in schools. One unexpected source that principals relied on was that of imagined law: they wrongly assumed that there was a law that guided them in the matter. The deployment of CCTV systems in Israeli schools is relatively new and takes place at an accelerated pace. School principals are the ones tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 43 publications
1
18
0
1
Order By: Relevance
“…Another type of condemnation concerned the parallels between school discipline and the criminal justice system, which can produce a criminalised self and social identity (Kupchik, 2010;Kayama et al, 2015). These contentions are related to the extensive 830 L. Perry-Hazan and N. Lambrozo use of criminal justice terminology (Kayama et al, 2015) and of school security measures (Perry-Hazan & Birnhack, 2016, 2018Birnhack et al, 2018).…”
Section: Due Process In Schools: Points Of Tension and Challengesmentioning
confidence: 99%
“…Another type of condemnation concerned the parallels between school discipline and the criminal justice system, which can produce a criminalised self and social identity (Kupchik, 2010;Kayama et al, 2015). These contentions are related to the extensive 830 L. Perry-Hazan and N. Lambrozo use of criminal justice terminology (Kayama et al, 2015) and of school security measures (Perry-Hazan & Birnhack, 2016, 2018Birnhack et al, 2018).…”
Section: Due Process In Schools: Points Of Tension and Challengesmentioning
confidence: 99%
“…Additional implications concern participation in decision making. The current study, along with our previous studies (Birnhack et al, 2018; Perry-Hazan & Birnhack, 2016), shows that students were not consulted or even informed about the cameras. Teachers were similarly excluded from decision-making processes regarding school CCTVs (Perry-Hazan & Birnhack, 2019).…”
Section: Discussionmentioning
confidence: 50%
“…Furthermore, the findings highlight the dissonance between the students’ perspectives regarding the legitimate usages of the CCTVs and the CCTVs’ actual usages. In a previous study, based on interviews with school principals, we found that although school security was a prominent consideration in the decision to install CCTVs (Perry-Hazan & Birnhack, 2016), many principals used CCTVs to gather evidence concerning minor disciplinary infringements (Perry-Hazan & Birnhack, 2018). This function creep is prohibited by European and Israeli law (GDPR, 2016, Art.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hardware Design yang digunakan adalah sebagai berikut: Garis panah diatas adalah Kabel Fiber Optic [21]. Masing-masing server diintegrasikan ke area-area di bawahnya adalah sebagai berikut:…”
Section: Hardware Designunclassified